Search for rare decays of D0 mesons into two muons - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; Li, Peilian; et al. (Physical review letters, 2023)
A search for the very rare 𝐷0→𝜇+⁢𝜇− decay is performed using data collected by the LHCb experiment in proton-proton collisions at √𝑠=7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The search is optimized for 𝐷0 mesons from 𝐷*+→𝐷0⁢𝜋+ decays but is also sensitive to 𝐷0 mesons from other sources. No evidence for an excess of events over the expected background is observed. An upper limit on the branching fraction of this decay is set at ℬ⁡(𝐷0→𝜇+⁢𝜇−)<3.1×10−9 at a 90% C.L. This represents the world’s most stringent limit, constraining models of physics beyond the standard model.
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 1055 weitere Personen]
Im Titel ist "0" hochgestellt
Veröffentlicht: 26. Juli 2023
Gesehen am 12.05.2025